Integrating Genomics and Clinical Data for Statistical Analysis by Using GEnome MINIng (GEMINI) and Fast Healthcare Interoperability Resources (FHIR): System Design and Implementation - Gründner, Julian; Wolf, Nicolas; Tögel, Lars; Haller, Florian; Prokosch, Hans-Ulrich; Christoph, Jan (Journal of Medical Internet Research, 2020)
Background: The introduction of next-generation sequencing (NGS) into molecular cancer diagnostics has led to an increase in the data available for the identification and evaluation of driver mutations and for defining personalized cancer treatment regimens. The meaningful combination of omics data, ie, pathogenic gene variants and alterations with other patient data, to understand the full picture of malignancy has been challenging.
CRIS-Team WoS Importer:2020-12-11